2014
DOI: 10.1103/physrevc.89.014613
|View full text |Cite
|
Sign up to set email alerts
|

Triton/3He ratio as an observable for neutron-skin thickness

Abstract: Based on the framework of the Isospin-Dependent Quantum Molecular Dynamics (IQMD) model in which the initial neutron and proton densities are sampled according to the droplet model, the correlation between triton-to-3 He yield ratio (R(t/ 3 He)=Yield(t)/Yield( 3 He)) and neutron skin thickness (δnp) in neutron-rich projectile induced reactions is investigated. By changing the diffuseness parameter of neutron density distribution in the droplet model for the projectile to obtain different δnp, the relationship … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…The initial configurations of projectile and target nuclei are expected to have considerable influences on the heavyion observables from transport simulations. For example, the uncertainties of the neutron skin thickness of initial nuclei may affect the neutron/proton yield ratio [198], the neutron-proton differential flow [199], the triton/ 3 He yield ratio [200], the π − /π + yield ratio [199,201], and other observables [202] related to the isospin dynamics in heavyion collisions. Generally, BUU-type codes use the initial density distribution from a Woods-Saxon parameterization, from a Skyrme-Hartree-Fock calculation [203], or from the Thomas-Fermi approximation [31,204].…”
Section: Initializationmentioning
confidence: 99%
“…The initial configurations of projectile and target nuclei are expected to have considerable influences on the heavyion observables from transport simulations. For example, the uncertainties of the neutron skin thickness of initial nuclei may affect the neutron/proton yield ratio [198], the neutron-proton differential flow [199], the triton/ 3 He yield ratio [200], the π − /π + yield ratio [199,201], and other observables [202] related to the isospin dynamics in heavyion collisions. Generally, BUU-type codes use the initial density distribution from a Woods-Saxon parameterization, from a Skyrme-Hartree-Fock calculation [203], or from the Thomas-Fermi approximation [31,204].…”
Section: Initializationmentioning
confidence: 99%
“…Then Ref. [22] indicated that the yield ratios of 3 H-3 He [R(t/ 3 He)] could be treated as another possible experimental observable to extract the proton skin thickness. Recently, Refs.…”
Section: Introductionmentioning
confidence: 99%
“…After initialization, the samples with satisfactory stability and expected neutron skin size will be selected as candidates for collisions, as described in Refs. [11,12]. Fig.…”
Section: A Dynamical Model: Iqmdmentioning
confidence: 99%
“…Details about the description of the IQMD model can be found in Refs. [11,12]. In the present work, the following potential is used,…”
Section: A Dynamical Model: Iqmdmentioning
confidence: 99%
See 1 more Smart Citation